1996
DOI: 10.1002/(sici)1097-0142(19960501)77:9<1844::aid-cncr13>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Invasive breast carcinoma: Analysis of dynamic magnetic resonance imaging enhancement features and cell proliferative activity determined by DNA S‐phase percentage

Abstract: Increased cell proliferation in invasive breast carcinoma, as determined by high DNA S-phase percentage, is significantly associated with a peripheral MRI enhancement pattern but unrelated to greater MRI enhancement amplitude, rate, or washout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Even so, our data suggest a value for the dynamic MRI in assessing the metastatic potential of breast carcinomas. In contrast, there was a significant and positive association between the rate of mitotic index and the peak of maximum intensity before two minutes, which is in accordance with previous studies reporting a positive association between MRI parameters and other proliferative parameters, such as high DNA S-phase percentage [28] or proliferative cellular activity as shown by proliferative nuclear antigen (PCNA) immunoreactivity [22]. Therefore our data appears to indicate that the proliferative activity and the invasive potential of cancerous cells could be, at least partially, unrelated processes.…”
Section: Discussionsupporting
confidence: 91%
“…Even so, our data suggest a value for the dynamic MRI in assessing the metastatic potential of breast carcinomas. In contrast, there was a significant and positive association between the rate of mitotic index and the peak of maximum intensity before two minutes, which is in accordance with previous studies reporting a positive association between MRI parameters and other proliferative parameters, such as high DNA S-phase percentage [28] or proliferative cellular activity as shown by proliferative nuclear antigen (PCNA) immunoreactivity [22]. Therefore our data appears to indicate that the proliferative activity and the invasive potential of cancerous cells could be, at least partially, unrelated processes.…”
Section: Discussionsupporting
confidence: 91%
“…It was also reported to be associated with high angiogenesis in the tumor periphery [23,24], but central tumor necrosis also accounted for this feature and may even be more important than MVD [45]. One study [46] showed a correlation between rim enhancement and high DNA S-phase percentage and suggested that rim enhancement is more often seen among rapidly growing cancers. Our results confirm that peripheral rim-like enhancement is not only a useful criterion for obtaining correct diagnosis, but is associated with the proliferative activity of the tumors.…”
Section: Mr Enhancement Morphologymentioning
confidence: 99%
“…New radiological modalities such as MRI and 99m Tc-sestamibi scintigraphy are under evaluation for the assessment and analysis of prognostic factors [11,19,20].…”
Section: Discussionmentioning
confidence: 99%